Manifestasi Budaya Literasi dalam Kegiatan Perpustakaan Masyarakat Studi pada Perpustakaan Omah Sinau Kelurahan Tanjung Sari Kecamatan Jambi Timur - Astuti, Wahyu Indri; Rum, Muhammad; Syamsuddin, Syamsuddin (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
ABSTRACT Intoduction. This study aims to determine the embodiment of literacy culture in the Community Library activities which were pioneered by the Omah Sinau Library in Tanjung Sari Village, Jambi Timur District. The importance of improving the literacy culture of the community is realized by the Omah Sinau library to answer the challenges of the times in the era of technological and information advancement. The existence of the Omah Sinau Library makes a positive contribution in providing sources of information and supporting skills activities for people of all ages and work backgrounds. Research methods. This study uses a qualitative method with a descriptive approach. Qualitative research methods are used for in-depth understanding of human and social problems, not describing the surface of a reality Data analysis. Data analysis using reduction, data presentation and conclusion drawing Results and Discussion. This research shows that the activities carried out by the Omah Sinau Library in Realizing a Literacy Culture for the Community are by providing literacy sources/reading materials; Making the library as a Media for Recreation/Entertainment; Making Libraries a Skills Education; Making the Library a Social Center for the Community. Conclusions and suggestions. The library's contribution to improving literacy culture has a very positive impact on the surrounding community. The role of libraries that make libraries as social centers of society is a new finding in this research that has not existed in the same type of research before. It is hoped that the existence of community libraries, especially in Jambi City, can increase in number and the Omah Sinau library can be used as a reference library whose activities support the improvement of literacy culture.